2008
DOI: 10.1007/s00270-008-9406-5
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Left Ventricular Outflow Pseudoaneurysm: Usefulness of Echocardiography and Multidetector Computed Tomography for Surgical Repair

Abstract: Left ventricular outflow tract (LVOT) pseudoaneurysm is a rare but potentially lethal complication, mainly after aortic root endocarditis or surgery. Usually it originates from a dehiscence in the mitral-aortic intervalvular fibrosa and it arises posteriorly to the aortic root. Due to these anatomical features, its imaging assessment is challenging and surgical repair requires complex procedures. An unusual case of LVOT pseudoaneurysm is described. It was detected by transthoracic ecocardiography 7 months afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The presence of right bundle branch block along with left axis deviation in the baseline electrocardiogram suggest erosion into the septal area by the LVOT pseudoaneurysm. Although transthoracic and transesophageal echocardiography can make a reliable diagnosis of LVOT pseudoaneurysm, 5) the patient in the present case had such a huge pseudoaneurysm that it required further imaging with computed tomography and invasive LV angiography along with coronary angiography. The natural history of LVOT pseudoaneurysm is not properly know.…”
mentioning
confidence: 70%
“…The presence of right bundle branch block along with left axis deviation in the baseline electrocardiogram suggest erosion into the septal area by the LVOT pseudoaneurysm. Although transthoracic and transesophageal echocardiography can make a reliable diagnosis of LVOT pseudoaneurysm, 5) the patient in the present case had such a huge pseudoaneurysm that it required further imaging with computed tomography and invasive LV angiography along with coronary angiography. The natural history of LVOT pseudoaneurysm is not properly know.…”
mentioning
confidence: 70%
“…Aortic PsA is a rare postoperative complication of cardiac surgery, probably due to graft infection, aortic dissection, connective tissue disorders, and excessive use of biologic glue [ 1 2 3 ]. It usually arises from a dehiscence in the mitral-aortic intervalvular fibrosa [ 8 ] and the most common site is previous aortic suture line after cardiac surgery. Development of the LVOT PsA, as in our case report, is very rare.…”
Section: Discussionmentioning
confidence: 99%
“…Frequently, IVMS aneurysm is an incidental finding in MDCT used for aortic valve surgery planning [ 17 ]. MDCT provides high resolution 3D anatomical details of interventricular septal defects, requiring less time and sedation than MR imaging, and also less post-processing time.…”
Section: Radiologic Techniquementioning
confidence: 99%
“…Choi et al reported no difference in morphology of IVMS aneurysms among patients with and without conduction abnormalities [ 12 , 18 ]. This aneurysm is distinguished from a diverticulum because it is surrounded by fibrous tissue instead of muscle [ 17 ].…”
Section: Radiologic Techniquementioning
confidence: 99%